First uncertainty evaluation of the FoCS-2 primary frequency standard - Jallageas, Antoine; Devenoges, Laurent; Petersen Mangin, Michael; Morel, J; Bernier, L. G; Schenker, Dominique; Thomann, Pierre; Südmeyer, Thomas (My University, 2018)
We report the uncertainty evaluation of the Swiss continuous primary frequency standard FoCS-2 (Fontaine Continue Suisse). Unlike other primary frequency standards which are working with clouds of cold atoms, this fountain uses a continuous beam of cold caesium atoms bringing a series of metrological advantages and specific techniques for the evaluation of the uncertainty budget. Recent improvements of FoCS-2 have made possible the evaluation of the frequency shifts and of their uncertainties in the order of 1 × 10−15. When operating in an optimal regime a relative frequency instability of 8 × 10−14 (τ/s) −1/2 is obtained. The relative standard uncertainty reported in this article, 1.99 × 10−15, is strongly dominated by the statistics of the frequency measurements.
Keywords: atomic clocks; primary frequency standards; continuous atomic fountain; caesium